(untitled) (European Journal of Pure and Applied Mathematics, 2025)
The notion of -stone ADLs is introduced, and their core properties are explored. It is shown that every -stone ADL is hemicomplemented but not vice versa. Several equivalent conditions are given for when a hemicomplemented ADL becomes -stone. Topological characterizations are provided via minimal prime -filters and their prime spectra.